IMPLEMENTASI PEMBIASAAN 5S (SENYUM, SALAM, SAPA, SOPAN, SANTUN) DALAM MEMBENTUK KARAKTER RELIGIUS - Novita Fitrotun Ni'mah; Partono (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This research aims to analyze the implementation of 5S (smile, greetings, greetings, polite, manner) in forming a Student Religious Character in SD 6 Gondosari. Character Education at Basic School is very important to form a positive attitude and behavior on students, one of which is through the expected 5S habits to form a religious character. This type of research is qualitative by using a descriptive qualitative approach. Data is collected through observation, interview, and documentation studies from primary and secondary sources. Data analysis is done through reduction stage, presentation, and verification. The results show that the 5S habits Have been applied consistently in the school environment, both in academic and academic activities and impact on the formation of a more polite attitude, mutual respect, and more than fourth. This habits not only enhance social behavior, but also strengthen the Student Religius Character.